Substrate film, laminate, and method for producing laminate
By controlling the surface distribution of silicon elements on the matrix film and applying appropriate alignment layer and optical opposite-sex film processes, the problem of unevenness of the liquid crystal layer when formed in the optical opposite-sex film is solved, and a more uniform liquid crystal layer and improved optical performance is achieved.
Patent Information
- Application Number
- JP2023141101
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2023-08-31
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2039-12-10
AI Technical Summary
In the prior art, uneven phase differences are prone to occur when the liquid crystal layer is formed in an optical opposite-sex film, resulting in visual unevenness.
The non-uniformity of the liquid crystal layer is suppressed by controlling the surface distribution of the silicon element on the matrix membrane, ensuring that its standard deviation is between 0.04 and 0.09, and using appropriate alignment layer and optical opposite film processes when applying the liquid crystal layer.
It effectively suppresses the unevenness of the liquid crystal layer, improves the optical performance, and reduces visual unevenness.
Smart Images

Figure 0007648697000002 
Figure 0007648697000003 
Figure 0007648697000004
Abstract
Description
[Technical field]
[0001] The present invention relates to a substrate film coated with a coating liquid containing a liquid crystal compound, a laminate including the same, and methods for producing these, as well as a method for inspecting the substrate film. [Background technology]
[0002] In display devices such as organic EL display devices and liquid crystal display devices, members including optically anisotropic films such as polarizing films and retardation films are used. As such optically anisotropic films, those in which a layer of a liquid crystal compound is formed on a substrate film are known. Patent Document 1 describes that a retardation layer is formed by applying a coating liquid containing a liquid crystal material onto a substrate film and curing it with ultraviolet light or the like. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2014-222282 A Summary of the Invention [Problem to be solved by the invention]
[0004] When a liquid crystal layer formed by curing a liquid crystal material applied onto a substrate film as described above is used as a retardation layer, retardation unevenness may be visually recognized in some cases.
[0005] An object of the present invention is to provide a base film, a laminate, and a method for producing the same, which are capable of suppressing unevenness occurring in a liquid crystal layer formed on the base film. [Means for solving the problem]
[0006] The present invention provides the following base film, laminate, and methods for producing and inspecting these. [1] A substrate film to which a coating liquid containing a liquid crystal compound is applied, A substrate film, wherein the standard deviation of the amount of silicon element on the surface on which the coating liquid is applied is 0.04 or more and 0.09 or less. [2] The substrate film according to [1], wherein the average amount of silicon element on the surface is 0.02 atomic % or more and 1.0 atomic % or less. [3] The substrate film according to [1] or [2], wherein the substrate film comprises at least one film selected from the group consisting of a cyclic polyolefin film, a polyester film, a cellulose ester film, and a poly(meth)acrylic acid film. [4] The substrate film according to any one of [1] to [3], wherein the substrate film has a thickness of 100 μm or less. [5] A laminate comprising the substrate film according to any one of [1] to [4] and a liquid crystal layer. [6] The laminate according to [5], wherein the liquid crystal layer is a cured layer of a polymerizable liquid crystal compound. [7] The laminate according to [5] or [6], further comprising an alignment layer between the substrate film and the liquid crystal layer. [8] A method for producing a substrate film, comprising the steps of: obtaining a substrate film to be coated with a coating liquid containing a liquid crystal compound from a pre-processed film, the method comprising the steps of: a step of contacting a roll with a surface of the unprocessed film, which is a side of the base film to be coated with the coating liquid, while transporting the unprocessed film; The tension per unit cross-sectional area of the unprocessed film in the contacting step is 1.0 N / mm 2 More than 2.5N / mm 2 The method for producing a base film is as follows. [9] Further, the step of cleaning the surface of the unprocessed film with a solvent after the step of contacting, and applying a heat of 200 W·min / m to the surface of the unprocessed film after the step of contacting. 2 and performing a corona treatment at the above treatment amount.
[10] A method for producing a substrate film, comprising the steps of: obtaining a substrate film to be coated with a coating liquid containing a liquid crystal compound from a pre-processed film, the method comprising the steps of: a step of contacting a roll with a surface of the unprocessed film, which is to be coated with the coating liquid, while transporting the unprocessed film; a step of cleaning the surface of the unprocessed film with a solvent after the step of contacting, and a step of applying a heat of 200 W·min / m to the surface of the unprocessed film after the step of contacting. 2 and a step of performing corona treatment at the above treatment amount.
[11] The method for producing a base film according to any one of [8] to
[10] , wherein the roll is a cleaning roll for removing foreign matter adhering to the surface of the unprocessed film.
[12] The method for producing a base film according to any one of [8] to
[11] , wherein at least a surface of the roll is made of silicone rubber.
[13] A method for producing a laminate including a base film and a liquid crystal layer, comprising the steps of: A method for producing a laminate, comprising a step of applying a coating liquid containing a liquid crystal compound to the base film according to any one of [1] to [4] or the base film produced by the method for producing a base film according to any one of [8] to
[12] .
[14] The liquid crystal compound is a polymerizable liquid crystal compound, The method for producing a laminate according to
[13] , further comprising the step of polymerizing and curing the polymerizable liquid crystal compound on the substrate film after the coating step.
[15] The method for producing a laminate according to
[14] , wherein the coating step includes a step of forming an alignment layer on the substrate film and coating the coating liquid on the alignment layer.
[16] A method for inspecting an element amount distribution of a specific element present on a surface of a substrate film to be coated with a coating liquid containing a liquid crystal compound, the method comprising the steps of: defining a plurality of measurement spots on the surface; calculating the amount of the specific element in each of the measurement spots by X-ray photoelectron spectroscopy; plotting the amount of the specific element at each of the measurement spots against the position of each of the measurement spots on the surface; and examining the element amount distribution of the specific element based on the results obtained by the plotting step.
[17] The method according to
[16] , wherein the setting step sets 50 or more measurement spots at regular intervals on the surface.
[18] The method according to
[16] or
[17] , wherein the inspecting step includes a step of calculating a standard deviation of the element amount of the specific element based on the result obtained by the plotting step, and inspecting the element amount distribution of the specific element based on the standard deviation.
[19] The method according to any one of
[16] to
[18] , wherein the specific element is at least one of Si and F. Effect of the Invention
[0007] According to the present invention, it is possible to provide a base film, a laminate, and a method for producing the same, which are capable of suppressing unevenness occurring in a liquid crystal layer formed on a base film. [Brief description of the drawings]
[0008] [Figure 1] FIG. 1 is a schematic cross-sectional view showing an example of a laminate of the present invention. [Diagram 2] FIG. 2 is a schematic cross-sectional view showing another example of the laminate of the present invention. [Diagram 3] FIG. 2 is a schematic cross-sectional view showing an example of a process for producing the base film of the present invention. [Figure 4] FIG. 2 is a schematic cross-sectional view showing another example of the manufacturing process for the base film of the present invention. [Diagram 5] FIG. 2 is a schematic cross-sectional view showing still another example of the process for producing the base film of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] Hereinafter, preferred embodiments of the substrate film, laminate, and manufacturing and inspection methods thereof of the present invention will be described with reference to the drawings.
[0010] <Base film> The base film of the present embodiment is a base film to which a coating liquid containing a liquid crystal compound is applied, and the standard deviation of the amount of silicon element on the surface to which the coating liquid is applied (hereinafter sometimes referred to as the "coating surface") is 0.04 or more and 0.09 or less.
[0011] The substrate film can serve as a coating layer formed by coating a coating liquid and as a support layer for a liquid crystal layer formed from the coating layer. When the liquid crystal compound contained in the coating liquid is a polymerizable liquid crystal compound, the substrate film is preferably used when polymerizing and curing the polymerizable liquid crystal compound in the coating liquid on the substrate film.
[0012] The standard deviation of the amount of silicon element on the coating surface of the substrate film may be 0.05 or more, 0.06 or more, or 0.08 or less. The silicon element attached to the coating surface of the substrate film may become a foreign matter of the substrate film. If the silicon element is unevenly distributed on the coating surface of the substrate film, the coating liquid applied to the coating surface is not uniformly applied, and it is considered that coating unevenness is likely to occur in the coating layer formed on the coating surface side of the substrate film. The coating unevenness occurring in the coating layer also appears as unevenness in the liquid crystal layer formed from the coating layer, and especially when the liquid crystal layer is a retardation layer, the unevenness is visually recognized as retardation unevenness. Such unevenness is likely to be a problem when a coating liquid containing a liquid crystal compound is applied on the substrate film. In the substrate film of this embodiment, as described above, the standard deviation of the amount of silicon element on the coating surface is set within the above range, so that unevenness can be suppressed from occurring in the coating layer formed on the substrate film, and unevenness occurring in the liquid crystal layer formed from the coating layer can also be suppressed. The standard deviation of the silicon element content can be calculated based on the results of X-ray photoelectron spectroscopy, and more specifically, can be determined by the method described in the examples below.
[0013] The average silicon element content on the coating surface of the substrate film is preferably 1.0 atomic% or less, more preferably 0.7 atomic% or less, even more preferably 0.5 atomic% or less, may be 0.4 atomic% or less, and may be 0.02 atomic% or more, may be 0.03 atomic% or more, or may be 0.04 atomic% or more. By having the average silicon element content on the coating surface of the substrate film within the above range, it is easy to suppress the occurrence of unevenness in the coating layer formed on the substrate film, and it is easy to suppress the occurrence of unevenness in the liquid crystal layer formed from the coating layer. The above average silicon element content can be calculated based on the results of X-ray photoelectron spectroscopy, and more specifically, it can be determined by the method described in the examples described below.
[0014] The substrate film is preferably a film formed of a resin material. For example, a resin material having excellent transparency, mechanical strength, thermal stability, stretchability, etc. is used as the resin material. For example, the substrate film may be a polyolefin film using a resin material such as polyethylene or polypropylene; a cyclic polyolefin film using a resin material such as norbornene-based polymer; a polyester film using a resin material such as polyethylene terephthalate or polyethylene naphthalate; a poly(meth)acrylic acid film using a resin material such as poly(meth)acrylic acid or polymethyl(meth)acrylate; a cellulose ester film using a resin material such as triacetyl cellulose, diacetyl cellulose, or cellulose acetate propionate; a vinyl alcohol film using a resin material such as polyvinyl alcohol or polyvinyl acetate; a polycarbonate film; a polystyrene film; a polyarylate film; a polysulfone film; a polyethersulfone film; a polyamide film; a polyimide film; a polyether ketone film; a polyphenylene sulfide film; a polyphenylene oxide film, and a mixture of these resin materials. Of these films, it is preferable to use any one of a cyclic polyolefin film, a polyester film, a cellulose ester film, and a poly(meth)acrylic acid film.
[0015] The substrate film may be a single layer of one or more resins, or may have a multi-layer structure of two or more layers. When the substrate film has a multi-layer structure, the resins constituting each layer may be the same or different, and may include a coated / cured layer such as a hard coat layer.
[0016] The base film may contain any additives, such as an ultraviolet absorbing agent, an antioxidant, a lubricant, a plasticizer, a release agent, a coloring inhibitor, a flame retardant, a nucleating agent, an antistatic agent, a pigment, and a colorant.
[0017] The thickness of the substrate film is not particularly limited, but may be 100 μm or less, 80 μm or less, 60 μm or less, 40 μm or less, 30 μm or less, and usually 1 μm or more, 5 μm or more, or 10 μm or more. The substrate film of this embodiment may be manufactured by contacting a roll with the surface of the pre-processed film to obtain the substrate film, as described later. If the thickness of the pre-processed film is thin, the pre-processed film is likely to stick to the roll. It is presumed that if the pre-processed film sticks to the roll, foreign matter such as roll chips and dirt attached to the roll due to deterioration of the roll is likely to be transferred to the surface of the pre-processed film, and the standard deviation of the silicon element amount on the coating surface of the substrate film is likely to become large. In the substrate film of this embodiment, the standard deviation of the silicon element amount on the coating surface is adjusted to be within a predetermined range as described above, thereby suppressing unevenness occurring in the liquid crystal layer formed on the coating surface side of the substrate film. As a result, even if the thickness of the substrate film is small, it can be suitably used to form a liquid crystal layer with suppressed unevenness.
[0018] A protective film may be laminated on one or both sides of the base film. The protective film is attached to the base film 11 by an adhesive layer of the protective film or by the adhesiveness of the protective film itself. As the protective film, for example, the protective film described below as the protective film provided on the laminate can be used.
[0019] <Laminate> 1 and 2 are schematic cross-sectional views showing an example of the laminate of this embodiment. As shown in FIG. 1, the laminate 10 includes the above-mentioned base film 11 and a liquid crystal layer 12. The liquid crystal layer 12 is provided on the coating surface 11a side of the base film 11. It can be formed from a coating layer formed by applying a coating liquid to the coating surface 11a side of the base film 11. When the liquid crystal compound contained in the coating liquid is a polymerizable liquid crystal compound, the liquid crystal layer 12 is preferably a cured layer of the polymerizable liquid crystal compound.
[0020] As described above, in the laminate 10, the standard deviation of the amount of silicon element on the coating surface 11a of the base film 11 is within the above range, so that unevenness occurring in the liquid crystal layer 12 formed by applying a coating liquid containing a liquid crystal compound to the coating surface 11a of the base film 11 can be suppressed.
[0021] 2, the laminate 10 may have an alignment layer 13 between the base film 11 and the liquid crystal layer 12. Even when the alignment layer 13 is provided between the base film 11 and the liquid crystal layer 12, when the liquid crystal layer 12 is formed on the coating surface 11a side of the base film 11 via the alignment layer 13, unevenness occurring in the liquid crystal layer 12 can be suppressed.
[0022] The laminate 10 may further have a protective film on the side of the base film 11 opposite to the liquid crystal layer 12, or may have a protective film on the side of the liquid crystal layer 12 opposite to the base film 11. The protective film is attached to the base film 11 or the liquid crystal layer 12 by an adhesive layer of the protective film or by the adhesiveness of the protective film itself.
[0023] (Liquid crystal layer) The liquid crystal layer 12 can be formed from a coating layer formed by coating a coating liquid containing a liquid crystal compound. When the coating liquid contains a polymerizable liquid crystal compound, the liquid crystal layer 12 may be a hardened layer of the polymerizable liquid crystal compound formed by polymerizing the polymerizable liquid crystal compound. The liquid crystal layer 12 may be a retardation layer, and the optical properties of the liquid crystal layer can be adjusted by the alignment state of the liquid crystal compound.
[0024] The polymerizable liquid crystal compound may be a rod-shaped polymerizable liquid crystal compound or a disk-shaped polymerizable liquid crystal compound. When a rod-shaped polymerizable liquid crystal compound is aligned horizontally or vertically to the base layer, the optical axis of the polymerizable liquid crystal compound coincides with the long axis direction of the polymerizable liquid crystal compound. When a disk-shaped polymerizable liquid crystal compound is aligned, the optical axis of the polymerizable liquid crystal compound is in a direction perpendicular to the disk surface of the polymerizable liquid crystal compound.
[0025] In order for the liquid crystal layer formed by polymerizing the polymerizable liquid crystal compound to exhibit an in-plane retardation, the polymerizable liquid crystal compound may be aligned in a suitable direction. When the polymerizable liquid crystal compound is rod-shaped, the in-plane retardation is exhibited by aligning the optical axis of the polymerizable liquid crystal compound horizontally to the substrate layer plane, in which case the optical axis direction and the slow axis direction coincide. When the polymerizable liquid crystal compound is disc-shaped, the in-plane retardation is exhibited by aligning the optical axis of the polymerizable liquid crystal compound horizontally to the substrate layer plane, in which case the optical axis and the slow axis are perpendicular to each other. The alignment state of the polymerizable liquid crystal compound can be adjusted by the combination of the alignment layer and the polymerizable liquid crystal compound.
[0026] The polymerizable liquid crystal compound is a compound having a polymerizable group and liquid crystallinity. The polymerizable group means a group involved in a polymerization reaction, and is preferably a photopolymerizable group. Here, the photopolymerizable group means a group that can be involved in a polymerization reaction by an active radical or an acid generated from a photopolymerization initiator described later. Examples of the polymerizable group include a vinyl group, a vinyloxy group, a 1-chlorovinyl group, an isopropenyl group, a 4-vinylphenyl group, an acryloyloxy group, a methacryloyloxy group, an oxiranyl group, and an oxetanyl group. Among them, an acryloyloxy group, a methacryloyloxy group, a vinyloxy group, an oxiranyl group, and an oxetanyl group are preferred, and an acryloyloxy group is more preferred. The liquid crystallinity of the polymerizable liquid crystal compound may be a thermotropic liquid crystal or a lyotropic liquid crystal, and when the thermotropic liquid crystal is classified according to the degree of order, it may be a nematic liquid crystal or a smectic liquid crystal.
[0027] As the rod-shaped polymerizable liquid crystal compound or the disk-shaped polymerizable liquid crystal compound, known compounds can be used. For example, compounds exemplified in JP2015-163937A, JP2016-42185A, WO2016 / 158940A, and JP2016-224128A can be used.
[0028] The thickness of the liquid crystal layer 12 is preferably 0.3 μm or more, may be 1 μm or more, and is usually 10 μm or less, may be 5 μm or less, and is preferably 3 μm or less. From the viewpoint of contributing to the thinning of the entire laminate 10, the thickness of the liquid crystal layer is preferably 5 μm or less, and more preferably 3 μm or less.
[0029] (Alignment layer) The alignment layer 13 has an alignment regulating force that aligns the liquid crystal compound contained in the liquid crystal layer 12 formed on the alignment layer 13 in a desired direction. Examples of the alignment layer 13 include an alignment polymer layer formed from an alignment polymer, a photoalignment polymer layer formed from a photoalignment polymer, and a groove alignment layer having a concave-convex pattern or a plurality of grooves on the layer surface, and the thickness of the alignment layer 13 is usually 10 to 4000 nm, and preferably 50 to 3000 nm.
[0030] The oriented polymer layer can be formed by applying a composition in which an oriented polymer is dissolved in a solvent to a substrate film, removing the solvent, and optionally performing a rubbing treatment. In the oriented polymer layer formed from the oriented polymer, the alignment control force can be arbitrarily adjusted depending on the surface state of the oriented polymer and the rubbing conditions.
[0031] The photo-alignable polymer layer can be formed by applying a composition containing a polymer or monomer having a photoreactive group and a solvent to the substrate film 11 and irradiating it with light such as ultraviolet light. In particular, when an alignment regulating force is to be exerted in the horizontal direction, the layer can be formed by irradiating it with polarized light. In the photo-alignable polymer layer, the alignment regulating force can be arbitrarily adjusted by irradiating the photo-alignable polymer with polarized light, etc.
[0032] The groove alignment layer can be formed, for example, by a method of forming an uneven pattern on the surface of a photosensitive polyimide film by exposing the surface of the film through an exposure mask having slits in a pattern shape, developing the film, etc.; a method of forming an uncured layer of active energy ray curable resin on a plate-shaped master having grooves on its surface, transferring this layer to the base film 11, and curing the layer; or a method of forming an uncured layer of active energy ray curable resin on the base film 11, and pressing a roll-shaped master having unevenness against the layer to form unevenness and then curing the layer.
[0033] (Protection film) The protective film may be a protective film substrate having a pressure-sensitive adhesive layer formed thereon, or may be a self-adhesive film.
[0034] The substrate for the protective film is preferably a resin film, and examples of the resin constituting the resin film include polyolefin resins such as polyethylene resins and polypropylene resins; cyclic polyolefin resins; polyester resins such as polyethylene terephthalate and polyethylene naphthalate; polycarbonate resins; and (meth)acrylic resins. Among these, polyester resins such as polyethylene terephthalate are preferred. The substrate for the protective film may have a single-layer structure, or may have a multi-layer structure of two or more layers.
[0035] The adhesive layer can be formed using a known adhesive. For example, an adhesive having a base polymer such as an acrylic, urethane, silicone, or polyvinyl ether adhesive can be used as the adhesive. In addition, it may be an active energy ray curable adhesive, a heat curable adhesive, or the like. Among these, an adhesive having an acrylic resin as a base polymer, which is excellent in transparency, adhesive strength, removability (hereinafter also referred to as reworkability), weather resistance, heat resistance, and the like, is preferable. The adhesive layer is preferably composed of a reaction product of an adhesive composition containing a (meth)acrylic resin, a crosslinking agent, and a silane compound, and may contain other components.
[0036] A self-adhesive film is a film that can adhere by itself and maintain its adhesion state without the need for a means for adhesion of an adhesive layer, etc. The self-adhesive film can be formed using, for example, a polypropylene-based resin, a polyethylene-based resin, or the like.
[0037] <Method of manufacturing base film> 3 to 5 are schematic cross-sectional views showing an example of a manufacturing process for the base film of this embodiment. The arrows in Figs. 3 to 5 indicate the transport direction of the unprocessed film. The manufacturing method for the base film of this embodiment is a manufacturing method for the base film 11, which obtains the base film 11 to be coated with a coating liquid containing a liquid crystal compound from the unprocessed film 21. The manufacturing method for the base film 11 includes at least one of the following steps [A] to [C].
[0038] Step [A] (Figure 3): The method includes a step of contacting a roll 25 with a surface 21a of the unprocessed film 21, which is the side of the base film 11 to be coated with the coating liquid, while transporting the unprocessed film 21; The tension per unit cross-sectional area of the unprocessed film 21 in the contact process is 1.0 N / mm 2 More than 2.5N / mm 2 The following is the result.
[0039] Step [B] (Figure 4): a step of bringing a roll 25 into contact with a surface 21a of the unprocessed film 21, which is the side of the base film 11 to be coated with the coating liquid, while transporting the unprocessed film 21; The method includes a step of cleaning the surface of the unprocessed film 21 with a solvent after the contacting step.
[0040] Step [C] (Figure 5): a step of bringing a roll 25 into contact with a surface 21a of the unprocessed film 21, which is the side of the base film 11 to be coated with the coating liquid, while transporting the unprocessed film 21; After the contact process, the surface of the unprocessed film 21 is subjected to a voltage of 200 W·min / m 2and performing a corona treatment at the above treatment amount.
[0041] In the above steps [A] to [C], the roll 25 that comes into contact with the surface 21a of the unprocessed film 21 (hereinafter, sometimes referred to as the "coating-side surface 21a of the unprocessed film 21"), which is the side of the base film 11 to be coated with the coating liquid, is not particularly limited. Examples of the roll 25 include a cleaning roll for removing foreign matter attached to the coating-side surface 21a of the unprocessed film 21, a transport roll for transporting the unprocessed film 21, a nip roll for controlling tension, and a spiral roll for transporting the unprocessed film 21 while suppressing wrinkles. The roll 25 is preferably a cleaning roll, and is preferably a roll having at least a surface formed of silicone rubber. The roll 25 may have adhesion capable of removing dirt and the like attached to the coating-side surface 21a of the unprocessed film 21.
[0042] If the method for producing the base film 11 includes a step of contacting the coating surface 21a of the unprocessed film 21 with the above-mentioned roll 25, silicon may adhere to the coating surface 11a of the produced base film 11. Therefore, in the method for producing the base film 11, by carrying out at least one of the above-mentioned steps [A] to [C], it becomes easier to adjust the standard deviation and / or average amount of elemental silicon on the coating surface 11a of the base film 11, and it can be adjusted to, for example, within the above-mentioned range.
[0043] Specifically, in the step [A], the tension per unit cross-sectional area of the unprocessed film 21 is set to 1.0 N / mm 2 More than 2.5N / mm 2 This makes it possible to reduce the force that presses the unprocessed film 21 against the surface of the roll 25 when the unprocessed film 21 comes into contact with the roll 25. Therefore, in the contacting step, roll chips resulting from deterioration of the roll 25, dirt adhering to the roll, and the like can be prevented from being transferred to the coating side surface 21a of the unprocessed film 21 and becoming foreign matter on the coating surface 11a of the base film 11.
[0044] The tension in step [A] is 1.2 N / mm 2 It may be 1.4N / mm or more. 2 It may be 2.3N / mm or more. 2 It may be less than 2.0N / mm 2 If the tension is too low, it becomes difficult to transport the unprocessed film 21 well, and if the tension is too high, the amount of roll chips, dirt, and the like adhering to the coating side surface 21a of the unprocessed film 21 increases.
[0045] In step [B], the coating surface 21a of the unprocessed film 21 is washed with a solvent after the contacting step. This makes it possible to remove the roll chips, dirt, and the like that have adhered to the coating surface 21a of the unprocessed film 21 in the contacting step by the solvent, thereby reducing the amount of foreign matter on the coating surface 11a of the base film 11.
[0046] The solvent used in the solvent washing in step [B] is not particularly limited as long as it does not dissolve the coating side surface 21a of the unprocessed film 21 or swell the unprocessed film 21. The solvent used in the solvent washing is preferably an organic solvent, and examples thereof include ketone-based organic solvents such as acetone, methyl isobutyl ketone (MIBK), methyl ethyl ketone (MEK), and cyclohexanone (anone); hydrocarbon-based organic solvents such as n-hexane, n-heptane, cyclohexane, methylcyclohexane, and ethylcyclohexane; aromatic organic solvents such as toluene and xylene; ether-based organic solvents such as diethyl ether and tetrahydrofuran (THF); alcohol-based organic solvents such as isopropyl alcohol (IPA), isobutyl alcohol (IBA), and n-butyl alcohol; and ester-based organic solvents such as ethyl acetate, isopropyl acetate, and butyl acetate. These organic solvents may be used alone or in combination of two or more.
[0047] The solvent cleaning in step [B] can be carried out, for example, using a solvent coating device 26 as shown in FIG. 4. Specifically, the solvent can be applied to the coating side surface 21a of the unprocessed film 21 in a predetermined thickness using the solvent coating device 26, and the applied solvent can be removed by drying. As a method for applying the solvent, a conventionally known method can be used, for example, a wire bar coating method, a direct gravure coating method, a reverse gravure coating method, etc. As a method for drying and removing the applied solvent, a conventionally known method can be used, for example, a method for drying by heating, a method for drying by suction under vacuum or low pressure, etc.
[0048] Alternatively, the solvent cleaning of step [B] may be performed by using a solvent application device 26 to spray a shower of solvent onto the application side surface 21a of the unprocessed film 21 to remove the roll chips, dirt, etc. adhering to the application side surface 21a.
[0049] In the step [C], after the step of contacting, a corona treatment device 27 is used to apply a voltage of 200 W·min / m to the coating side surface 21a of the unprocessed film 21. 2 Corona treatment is performed with the above treatment amount. This makes it possible to remove the roll chips and dirt adhering to the coating side surface 21a of the unprocessed film 21 in the contact step, and to reduce the amount of foreign matter on the coating surface 11a of the base film 11.
[0050] The corona treatment rate in process [C] is 210 W·min / m 2 More than 220W·min / m 2 It can be more than 350W·min / m 2The corona treatment in step [C] may be performed once with the above treatment amount, or may be performed two or more times so that the total treatment amount falls within the above range. If the corona treatment in step [C] is too strong, there is a risk that the unprocessed film 21 will be deteriorated by the corona treatment, and if the corona treatment amount in step [C] is too small, it will be difficult to reduce the amount of roll chips, dirt, and the like adhering to the coating side surface 21a of the unprocessed film 21.
[0051] The tension per unit cross-sectional area of the unprocessed film 21 in the contacting step of step [B] and step [C] may be the same as the tension described in the above step [A], or may be greater than the tension described in the above step [A]. For example, the tension per unit cross-sectional area of the unprocessed film 21 in the contacting step of step [B] and step [C] is 1.0 N / mm 2 It may be 2.0N / mm or more. 2 It may be 2.5N / mm or more. 2 It may be 2.7N / mm or more. 2 It may be more than 5.0N / mm 2 Less than 4.0N / mm 2 It may be the following.
[0052] The method for producing the base film 11 of this embodiment may include at least one of the above steps [A] to [C], but two or more of these steps may be combined, or the same step may be performed two or more times. When two or more of the above steps [A] to [C] are combined, the step of washing with a solvent in the above step [B] and / or the step of performing corona treatment in the above step [C] may be performed under the tension per unit cross-sectional area condition of the above step [A], or after the step of contacting the roll as described in the above step [B] or the above step [C]. When both the step of washing with a solvent and the step of performing corona treatment are performed, the order of performing each step is not particularly limited.
[0053] The pre-processed film used in the above-mentioned manufacturing method is preferably a film formed using the resin material constituting the base film. The layer structure and thickness of the pre-processed material film include the layer structure and thickness described for the base film.
[0054] The base film 11 produced by the above-mentioned production method is preferably a method for producing a base film having a standard deviation of the silicon element content on the coating surface of 0.04 to 0.09, and the average silicon element content on the coating surface is preferably 0.02 atomic % to 1.0 atomic %. Examples of the resin material constituting the base film 11 include those mentioned above.
[0055] When the base film 11 is a long body, the manufacturing method of the base film 11 is preferably performed by so-called roll to roll. Specifically, it is preferable to unwind the pre-processing film 21 from a roll body in which the pre-processing film 21 is wound in a roll shape, and to bring the roll 25 into contact with the pre-processing film 21. The pre-processing film 21 in contact with the roll 25 may be wound into a roll shape again. When performing the step [B] or the step [C], the pre-processing film 21 may be once wound into a roll shape after the above-mentioned contacting step, and then unwound from the roll and subjected to solvent cleaning or corona treatment, or the pre-processing film 21 may be subjected to solvent cleaning or corona treatment without being wound into a roll shape after the above-mentioned contacting step, and then wound into a roll shape. Alternatively, the manufactured base film 11 may be provided to the manufacturing step of the laminate 10 described later without being wound into a roll shape again.
[0056] The manufacturing method of the base film 11 may include a step of laminating a protective film on one or both sides of the unprocessed film 21, or may include a step of laminating a protective film on one or both sides of the base film 11. The protective film is laminated to the unprocessed film 21 by an adhesive layer of the protective film or by the adhesiveness of the protective film itself.
[0057] The step of laminating a protective film to the unprocessed film 21 can include a step of laminating a protective film to the coating surface 21a side of the unprocessed film 21 and / or a step of laminating a protective film to the surface opposite to the coating surface 21a of the unprocessed film 21. The step of laminating a protective film to the base film 11 can include a step of laminating a protective film to the coating surface 11a side of the base film 11 and / or a step of laminating a protective film to the surface opposite to the coating surface 11a of the base film 11.
[0058] The step of laminating a protective film on the unprocessed film 21 may be performed before or after the step of abutting the coating side surface 21a of the unprocessed film 21 with the roll 25. When a protective film is laminated on the coating side surface 21a of the unprocessed film 21, the protective film laminated on the coating side surface 21a may be peeled off once before the above-mentioned abutting step is performed, and the protective film may be laminated again after the above-mentioned abutting step is performed. Alternatively, the protective film may be laminated after the base film 11 is obtained. As the protective film, for example, the one described above as the protective film provided on the laminate may be used.
[0059] <Method of manufacturing laminate> The method for producing the laminate 10 of this embodiment includes a step of applying a coating liquid containing a liquid crystal compound to the above-mentioned base film 11 or to the base film 11 produced by the above-mentioned production method. The coating liquid is applied to the coating surface 11a side of the base film 11, and the liquid crystal layer 12 can be formed from a coating layer formed by applying the coating liquid.
[0060] When the liquid crystal compound contained in the coating liquid is a polymerizable liquid crystal compound, it is preferable to include a step of polymerizing and curing the polymerizable liquid crystal compound on the coating surface 11a side of the base film 11. The coating step may include a step of forming an alignment layer 13 on the base film 11 and coating the coating liquid on the alignment layer 13.
[0061] When the above-mentioned base film 11 is used, the standard deviation of the silicon element amount on the coating surface 11a is adjusted to a predetermined range. In addition, the base film 11 manufactured by the above-mentioned manufacturing method has a reduced amount of foreign matter adhering to the coating surface 11a. This makes it possible to suppress the occurrence of coating unevenness in the coating layer formed by applying a coating liquid containing a liquid crystal compound to the coating surface 11a of the base film 11 without or through the alignment layer 13, and to suppress the occurrence of unevenness in the liquid crystal layer 12 formed from the coating layer.
[0062] The coating liquid used in the step of applying the coating liquid contains a liquid crystal compound, and may further contain a solvent, a polymerization initiator, a reactive additive, a polymerization inhibitor, etc. As for the solvent, polymerization initiator, reactive additive, polymerization inhibitor, etc., those exemplified in JP2015-163937A, JP2016-42185A, WO2016 / 158940A, and JP2016-224128A can be used.
[0063] The coating liquid can be applied by a known method, for example, a coating method such as a spin coating method, an extrusion method, a gravure coating method, a die coating method, a slit coating method, a bar coating method, or an applicator method, or a printing method such as a flexography method.
[0064] When the coating liquid contains a solvent, the step of coating the coating liquid may include a drying step for removing the solvent contained in the coating layer. When the coating liquid contains a polymerizable liquid crystal compound, the drying step is preferably performed under conditions in which the polymerizable liquid crystal compound does not polymerize. Examples of the drying method include natural drying, ventilation drying, heat drying, and reduced pressure drying.
[0065] The step of polymerizing and curing the polymerizable liquid crystal compound can be carried out by a known method of polymerizing a compound having a polymerizable functional group. Examples of the polymerization method include thermal polymerization and photopolymerization, and photopolymerization is preferable from the viewpoint of ease of polymerization. When polymerizing the polymerizable liquid crystal compound by photopolymerization, it is preferable to use a coating liquid containing a photopolymerization initiator, apply this coating liquid, dry it, align the polymerizable liquid crystal compound contained in the dried coating film after drying, and perform photopolymerization while maintaining this liquid crystal alignment state.
[0066] Photopolymerization can be carried out by irradiating the polymerizable liquid crystal compound in the dried film with active energy rays. The active energy rays to be irradiated can be appropriately selected depending on the type and amount of polymerizable groups in the polymerizable liquid crystal compound, the type of photopolymerization initiator, etc., and can include, for example, one or more active energy rays selected from the group consisting of visible light, ultraviolet light, laser light, X-rays, α-rays, β-rays, and γ-rays. Among these, ultraviolet light is preferred because it is easy to control the progress of the polymerization reaction and photopolymerization devices that are widely used in this field can be used, and it is preferable to select the type of polymerizable liquid crystal compound and photopolymerization initiator so that photopolymerization can be performed by ultraviolet light. In photopolymerization, the polymerization temperature can also be controlled by irradiating the active energy rays while cooling the dried film with an appropriate cooling means.
[0067] When the coating step includes a step of forming an alignment layer 13 on the substrate film 11 and coating the coating liquid on the alignment layer 13, the alignment layer 13 may be an alignable polymer layer, a photoalignable polymer layer, or a groove alignment layer, as described above. Examples of the method for coating the coating liquid on the alignment layer 13 include the methods described above.
[0068] <Inspection method for base film> The inspection method of the present embodiment is a method for inspecting the element amount distribution of a specific element present on a surface (coating surface) 11a of a substrate film 11 to which a coating liquid containing a liquid crystal compound is applied. Setting a plurality of measurement spots on the coating surface 11a; calculating an amount of a specific element in each of the plurality of measurement spots by X-ray photoelectron spectroscopy; Plotting the amount of a specific element at each of a plurality of measurement spots on the coating surface 11a against the position of the measurement spot; and inspecting the element amount distribution of the specific element based on the results obtained by the plotting step.
[0069] In the setting step, a plurality of measurement spots for calculating the element amount of a specific element by X-ray photoelectron spectroscopy (hereinafter, sometimes referred to as "XPS analysis") are set on the coating surface 11a of the base film 11. The measurement spots may be set on the entire base film 11 for inspecting the element amount distribution, or may be set within a measurement area set in a part of the base film. It is preferable that a plurality of measurement spots are provided, and the plurality of measurement spots are preferably provided at equal intervals. The number of measurement spots may be, for example, 50 or more, 70 or more, 90 or more, or 100 or more. If the number of measurement spots is too small, the accuracy of inspecting the element amount distribution of the specific element is likely to decrease, and if the number of measurement spots is too large, it takes a long time to measure the element amount of the specific element for all the set measurement spots.
[0070] The size of the measurement spot is not particularly limited, and may be, for example, 0.2 mm or more in diameter, 0.4 mm or more, and usually 0.8 mm or less, and may be 0.6 mm or less. The pitch of the measurement spots (the distance between the centers of adjacent measurement spots) may be 0.2 mm or more, 0.4 mm or more, and 0.6 mm or more, and usually 1.5 mm or less, 1.2 mm or less, and may be 1.0 mm or less. The size of the measurement area in which the measurement spots are set in the base film 11 is also not particularly limited, and may be, for example, 15 mm in the length direction × 5 mm in the width direction to 60 mm in the length direction × 20 mm in the width direction. By having the number, size, and pitch of the measurement spots and the size of the measurement area within the above ranges, for example, when a liquid crystal layer 12 is formed by applying a coating liquid containing a liquid crystal compound onto the coating surface 11a of the base film 11, it is possible to suitably inspect whether the base film 11 is one in which the liquid crystal layer 12 in which the generation of unevenness is suppressed is easily formed.
[0071] In the calculating step, the amount of the specific element in each of the measurement spots set in the setting step is calculated by XPS analysis. The amount of the specific element by XPS analysis may be calculated by a known method using an X-ray photoelectron spectrometer.
[0072] In the plotting step, the amount of the specific element in each measurement spot is plotted for each position of the measurement spot. The plotting step can be performed, for example, by mapping in which the positions of the measurement spots in the measurement region are set in a two-dimensional plane, and the amount of the specific element is set and plotted in a direction perpendicular to the two-dimensional plane.
[0073] In the inspecting step, the element amount distribution of the specific element is inspected based on the plot (e.g., mapping) result obtained in the plotting step. In the inspecting step, the standard deviation of the element amount of the specific element and the average element amount of the specific element are calculated based on all the plots obtained in the plotting step, or based on the plots at each measurement spot present within an arbitrary range in the two-dimensional plane. This makes it possible to inspect the magnitude of variation in the element amount distribution on the coating surface 11a of the base film 11 based on the standard deviation of the element amount of the specific element and the average element amount of the specific element.
[0074] For example, when the manufacturing method of the base film 11 described above includes a step of contacting the coating surface 11a of the base film 11 with the roll 25, it is considered that the contact position between the coating surface 11a of the base film 11 and the roll 25 does not change significantly in the direction perpendicular to the conveying direction of the base film 11 (width direction), and therefore the element amount distribution of a specific element in the width direction of the base film 11 also does not change significantly depending on the position in the conveying direction. Therefore, as described above, when inspecting the element amount distribution of silicon on the coating surface 11a of the base film 11, it is preferable to calculate the standard deviation and average silicon amount based on a plot of the element amount of silicon in the width direction of the base film 11.
[0075] The elements of the element amount distribution to be inspected in the above inspection method are not particularly limited as long as they can be analyzed by XPS analysis. For example, in order to detect foreign matter present on the coating surface 11a of the base film 11 as described above, it is preferable to detect Si (silicon) element or F (fluorine) element.
[0076] Using the above inspection method, for example, the standard deviation or average silicon amount of the silicon element on coating surface 11a of base film 11 can be determined to inspect the element amount distribution of silicon element on coating surface 11a of base film 11. This makes it possible to determine whether or not unevenness is likely to occur in liquid crystal layer 12 when liquid crystal layer 12 is formed by coating coating surface 11a of base film 11 with a coating liquid containing a liquid crystal compound, and makes it easier to form liquid crystal layer 12 on base film 11 with reduced unevenness. EXAMPLES
[0077] The present invention will be described in more detail below with reference to examples and comparative examples, but the present invention is not limited to these examples. In the examples and comparative examples, "%" and "parts" are by mass % and parts by mass unless otherwise specified.
[0078] [Calculation of standard deviation and average silicon content] The standard deviation and average silicon content of the silicon element were calculated by X-ray photoelectron spectroscopy using an X-ray photoelectron spectrometer (K-Alpha, manufactured by Thermo Scientific). Specifically, on the coating surface of the base film, 50 measurement spots were set at 0.6 mm scanning intervals (distance between the centers of the measurement spots) in the X direction (direction (width direction) perpendicular to the conveying direction of the base film) and 20 measurement spots were set at 0.6 mm scanning intervals in the Y direction (conveying direction of the base film), and the elemental content of silicon in each of the measurement spots was calculated for a measurement area of about 30 mm (X direction) × about 12 mm (Y direction).
[0079] The calculated amount of silicon element was plotted against the position of each measurement spot on the XY plane, and mapping was performed. Three straight lines parallel to the X direction (width direction of the base film) were set so as to equally divide the range of the Y direction (transport direction of the base film) of this XY plane into four, and the standard deviation of the amount of silicon element on each line and the average value of the amount of silicon element on each line were calculated based on the amount of silicon element (plotted values) of each measurement spot (all measurement spots in the X direction) located on each line. The average values obtained were used as the standard deviation of the amount of silicon element on the base film and the average amount of silicon element.
[0080] (Measurement Procedure) First, a wide scan spectrum was obtained for each measurement spot, and narrow scan spectra were obtained for all elements detected in the wide scan spectrum. Next, the peak areas of the narrow scan spectra for all elements were obtained, the elemental composition ratio (Atomic%) for each measurement spot was calculated, and the elemental amount of silicon for each measurement spot was calculated.
[0081] (Measurement conditions) X-ray source: Al-Kα monochromatic (1486.7 eV) X-ray spot size (diameter of measurement spot): 400μm Wide-scan analysis (Survey scan); Measurement range: -10 to 1350 eV, pass energy: 200 eV, Dwell time: 25 ms, step: 1.0 eV, number of integrations: 5 · Narrow scan analysis (Snap scan); Pass energy: 150 eV, acquisition time: 1 second, number of integrations: 10
[0082] [Observation of phase difference unevenness] (Preparation of polarizing plate) A 20 μm thick polyvinyl alcohol film (average polymerization degree about 2400, saponification degree 99.9 mol% or more) was uniaxially stretched about 4 times by dry stretching, and then immersed in pure water at 40 ° C for 40 seconds while maintaining tension, and then immersed in an aqueous solution with a mass ratio of iodine / potassium iodide / water of 0.052 / 5.7 / 100 at 28 ° C for 30 seconds to perform a dyeing treatment. Then, immersed in an aqueous solution with a mass ratio of potassium iodide / boric acid / water of 11.0 / 6.2 / 100 at 70 ° C for 120 seconds. After washing with pure water at 8 ° C for 15 seconds, it was dried at 60 ° C for 50 seconds and then at 75 ° C for 20 seconds while maintaining a tension of 300 N to obtain an absorptive polarizing film with a thickness of 8 μm in which iodine was adsorbed and aligned on the polyvinyl alcohol film. An aqueous adhesive consisting of an aqueous solution of a polyvinyl alcohol-based resin was applied to both sides of the obtained polarizing film, and a protective film (ZEONOR ZF14, a COP film manufactured by ZEON) was laminated to one side of the polarizing film, and a protective film (FUJITAC TJ25, a TAC film manufactured by FUJIFILM) was laminated to the other side to obtain a polarizing plate having protective films on both sides.
[0083] (Observation of phase difference unevenness) On the backlight, two polarizing plates having a protective film on one side obtained by peeling off the TAC film from the polarizing plate obtained above (hereinafter, sometimes referred to as "polarizing plates with one-sided protective film") were placed so that the polarizing film sides of each were facing each other and the absorption axes were in a cross-Nicol relationship perpendicular to each other. A laminate obtained by peeling off the protective film [2] from the laminate with protective film obtained in each Example and Comparative Example was placed between these two polarizing plates with one-sided protective film so as to face the two polarizing plates with one-sided protective film. In this state, the backlight was turned on, and the laminate was rotated in the plane while observing the light transmitted from the backlight through the polarizing plate with one-sided protective film, the laminate, and the polarizing plate with one-sided protective film from the front with the naked eye, and was fixed at the position where the transmitted light was the darkest. At this fixed position, the polarizing plate with one-sided protective film farthest from the backlight was visually inspected from the front at an angle of 30 to 60 degrees to confirm phase difference unevenness (unevenness in shading).
[0084] Comparative Example 1 (Preparation of base film) A protective film [1] (a polyethylene terephthalate resin film having an adhesive layer) was attached to one side of a long pre-processed film (a cyclic olefin film manufactured by Zeon Corporation, thickness 20 μm) via the adhesive layer of the protective film [1]. Next, a cleaning roll with a surface made of silicone rubber was brought into contact with the surface (coating side surface) of the pre-processed film opposite the protective film [1], to clean the coating side surface of the pre-processed film. In the area where the cleaning roll was brought into contact, the tension per unit cross-sectional area of the pre-processed film (transport tension) was 3.0 N / mm 2 The coating surface of the unprocessed film that had been cleaned was applied with a 20 W·min / m 2 A corona treatment was carried out at a treatment amount of 1000 to obtain a substrate film.
[0085] A self-adhesive polyethylene resin film, protective film [2], was attached to the corona-treated surface (coated surface) of the substrate film obtained above, and the substrate film with protective film was then wound up into a roll. The protective film [2] was peeled off from the substrate film with protective film, and the silicon element amount and the standard deviation of the silicon element amount on the corona-treated surface (coated surface) were calculated. The results are shown in Table 1.
[0086] (Formation of alignment layer) 10.0 parts of diethylene glycol di(meth)acrylate (Shin-Nakamura Chemical Co., Ltd., A-600), 10.0 parts of trimethylolpropane triacrylate (Shin-Nakamura Chemical Co., Ltd., A-TMPT), 10.0 parts of 1,6-hexanediol di(meth)acrylate (Shin-Nakamura Chemical Co., Ltd., A-DCP), and 1.5 parts of Irgacure 907 (BASF, Irg-907) as a photopolymerization initiator were dissolved in 70.0 parts of methyl ethyl ketone as a solvent to prepare a coating solution for forming an alignment layer.
[0087] The protective film [2] attached to the substrate film prepared above is peeled off, and the coating liquid for forming the alignment layer is applied to the peeled surface to form a coating layer. After drying by heat treatment at a temperature of 80°C for 60 seconds, ultraviolet rays (UVB) are irradiated at 220 mJ / cm. 2 The monomer components contained in the coating solution for forming the alignment layer were polymerized and cured by irradiation, thereby forming an alignment layer having a thickness of 0.5 μm on the coated surface of the substrate film.
[0088] (Formation of liquid crystal layer) A coating solution for forming a liquid crystal layer was prepared by dissolving 20.0 parts of a photopolymerizable nematic liquid crystal compound (RMM28B, manufactured by Merck) and 1.0 part of Irgacure 907 (Irg-907, manufactured by BASF) as a photopolymerization initiator in 80.0 parts of propylene glycol monomethyl ether acetate as a solvent.
[0089] On the alignment layer formed on the substrate film, a coating liquid for forming a liquid crystal layer is applied to form a coating layer, which is then dried by heat treatment at a temperature of 80°C for 60 seconds, and then exposed to ultraviolet light (UVB) at 220 mJ / cm. 2 The liquid crystal compound was polymerized and cured by irradiation to form a liquid crystal layer having a thickness of 1.0 μm. The liquid crystal layer was a retardation layer exhibiting birefringence in the thickness direction.
[0090] Next, the protective film [1] attached to the base film was peeled off, and a protective film [2] was attached to the side of the liquid crystal layer opposite the alignment layer, to obtain a laminate with a protective film in which the base film, alignment layer, liquid crystal layer, and protective film [2] were laminated in this order. The laminate obtained from the resulting laminate with the protective film was used to observe the phase difference unevenness. The results are shown in Table 1.
[0091] [Examples 1 and 2] A laminate with a protective film was obtained in the same manner as in Comparative Example 1, except that in the preparation of the base film, the tension per unit cross-sectional area of the unprocessed film in the area where the cleaning roll was in contact (transport tension) and the amount of corona treatment on the coating side surface of the unprocessed film that had been subjected to cleaning treatment were changed as shown in Table 1. Table 1 shows the results of calculating the amount of silicon element and the standard deviation of the amount of silicon element on the corona-treated surface (coating surface) of the base film, and the results of observing the retardation unevenness using the laminate obtained from the laminate with the protective film.
[0092] Example 3 In the preparation of the substrate film, cleaning and corona treatment were performed in the same manner as in Comparative Example 1, and a protective film [2] was attached to the corona-treated surface. Thereafter, the protective film [2] was peeled off, and methyl ethyl ketone (MEK) was applied to the exposed surface (corona-treated surface) to a thickness of 20 μm, and solvent cleaning was performed by drying at a temperature of 80° C. for 2 minutes to obtain a substrate film. Using this substrate film, a substrate film with a protective film was obtained in the same manner as in Comparative Example 1, and this was wound up in a roll. The results of calculating the silicon element amount and the standard deviation of the silicon element amount on the solvent-cleaned surface (coated surface) of the substrate film, and the results of observing the retardation unevenness using the laminate obtained from the laminate with the protective film are shown in Table 1.
[0093] [Table 1] [Explanation of symbols]
[0094] 10 laminate, 11 base film, 11a coating surface, 12 liquid crystal layer, 13 alignment layer, 21 film before processing, 21a coating side surface, 25 roll, 26 solvent coating device, 27 corona treatment device.
Claims
1. A substrate film to which a coating liquid containing a liquid crystal compound is applied, A substrate film in which the standard deviation of the amount of silicon element on the surface on which the coating liquid is applied is 0.04 to 0.09 (excluding substrate films on which a clear anti-reflective layer containing a silicone-based leveling agent is formed on the surface opposite to the surface on which the coating liquid is applied).
2. 2. The substrate film according to claim 1, wherein the average amount of silicon element on the surface is 0.02 atomic % or more and 1.0 atomic % or less.
3. The substrate film according to claim 1 or 2, wherein the substrate film comprises at least one film selected from the group consisting of a cyclic polyolefin-based film, a polyester-based film, a cellulose ester-based film, and a poly(meth)acrylic acid-based film.
4. The substrate film according to any one of claims 1 to 3, wherein the substrate film has a thickness of 100 µm or less.
5. A laminate comprising the substrate film according to any one of claims 1 to 4 and a liquid crystal layer.
6. The laminate according to claim 5 , wherein the liquid crystal layer is a cured layer of a polymerizable liquid crystal compound.
7. The laminate according to claim 5 or 6, further comprising an alignment layer between the substrate film and the liquid crystal layer.
8. A method for producing a laminate including a substrate film and a liquid crystal layer, comprising the steps of: A method for producing a laminate, comprising a step of applying a coating liquid containing a liquid crystal compound to the substrate film according to any one of claims 1 to 4.
9. the liquid crystal compound is a polymerizable liquid crystal compound, The method for producing a laminate according to claim 8 , further comprising the step of polymerizing and curing the polymerizable liquid crystal compound on the substrate film after the coating step.
10. The method for producing a laminate according to claim 9 , wherein the coating step includes a step of forming an alignment layer on the substrate film, and coating the coating liquid on the alignment layer.
Citation Information
Patent Citations
Transfer body for optical film, optical film, image display device, manufacturing method of transfer body for optical film, and manufacturing method of optical film
JP2014222282A
Production method of patterned retardation film
JP2015025969A